Multifractal detrended fluctuation analysis approach to study period of crisis of YES bank (Nonlinear Studies, 2021)
To examine different latent characteristics of a given time series several methods are available. Here we have used Multifractal Detrended Fluctuation Analysis (MFDFA) method for the analysis of YES bank time series of closing prices from the duration of 9th July 2014 to 9th April 2020. We found that during period of crisis, time series is extremely multifractal and consequently the strength of multifractality also increases and reaches close to unity. We also observe decrease in efficiency during this period. We therefore, conclude that multifractality can be used as one of the parameter for prediction of stability of banking sector.